Strengthen Arctic Governance to Stop Russian and Chinese Overreach - Vicik, Mark T. (USAWC Press, 2022)
This article argues shortfalls in the international institutions governing the Arctic have allowed Russia and China to expand control over the region. It provides an overview of regional governance and power dynamics, outlines a three-part approach to correcting deficiencies, highlights attempts by Russia and China to circumvent international governance, examines how the Arctic’s governing institutions address Russian and Chinese growth in the region, and focuses on the institutional failures that have allowed Russia and China to expand—failures academic scholarship and US policy have not adequately addressed. Practitioners will find specific steps for rectifying issues with Arctic institutions to support the United States’ interests in the region.